Dynamic efficiency and price leadership in the DAX-future and the DAX cash market: An empirical investigation - Frederic Merz (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1994)
This paper provides results of an empirical study, adressing both the question of the efficiency of the DAX-fFuture market concerning its risk transfer function and the question of price leadership. For determining the pricing relationship between the futures and the cash market, co-integration analysis and nonlinear least squares estimation methods are applied. Results indicate that the pricing relationship is closely related to the cost-of-carry model and co-integrated. It will be shown that the cash market leads the futures market.
Keywords: 330; Index-Futures; Aktienindex; Effizienzmarkthypothese; Deutschland